2009
DOI: 10.1523/jneurosci.4172-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Antipsychotic Risperidone on Dopamine Synthesis in Human Brain Measured by Positron Emission Tomography with l-[β-11C]DOPA: A Stabilizing Effect for Dopaminergic Neurotransmission?

Abstract: receptors corresponding dose of risperidone was observed, the changes in dopamine synthesis capacity by the administration of risperidone were not significant, nor was the relation between the occupancy of dopamine D 2 receptors and these changes. A significant negative correlation was observed between the baseline dopamine synthesis capacity and the changes in dopamine synthesis capacity by risperidone, indicating that this antipsychotic can be assumed to stabilize the dopamine synthesis capacity. The therape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
27
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 42 publications
6
27
0
Order By: Relevance
“…They concluded that stimulated and baseline DA release were both increased and positively correlated in drug-naïve patients but not in healthy controls, suggesting that storage capacity in presynaptic nerves is associated with the disorder and is consistent with increased midbrain DA neuron activity. It is interesting to note that Ito et al (2009) obtained a significant negative correlation between baseline DA synthesis capacity and changes in DA synthesis capacity following a single oral dose of risperidone in healthy male volunteers on separate days, thereby indicating that the antipsychotic compound may be assumed to stabilize DA synthesis capacity.…”
Section: Da In Schizophrenia Spectrum Disordersmentioning
confidence: 98%
“…They concluded that stimulated and baseline DA release were both increased and positively correlated in drug-naïve patients but not in healthy controls, suggesting that storage capacity in presynaptic nerves is associated with the disorder and is consistent with increased midbrain DA neuron activity. It is interesting to note that Ito et al (2009) obtained a significant negative correlation between baseline DA synthesis capacity and changes in DA synthesis capacity following a single oral dose of risperidone in healthy male volunteers on separate days, thereby indicating that the antipsychotic compound may be assumed to stabilize DA synthesis capacity.…”
Section: Da In Schizophrenia Spectrum Disordersmentioning
confidence: 98%
“…Moreover, it also has a high-affinity antagonist effect for the serotonin type 2 (5HT 2 ), α 1 and α 2 adrenergic, and H1 histaminergic receptors7. The antagonist effects were found in both in vitro and in vivo studies 8,9. Furthermore, new mechanism as partial uncompetitive inhibition on D-amino acid oxidase (DAO) was investigated.…”
Section: Pharmacokinetic and Pharmacodynamic Profile Of Risperidonementioning
confidence: 99%
“…Similar experimental protocol as previous our work with risperidone was used, and results were compared [14].…”
Section: Introductionmentioning
confidence: 99%